2009
DOI: 10.4049/jimmunol.0803282
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin 2 Is Required for Pulmonary Host Defense against Klebsiella Infection

Abstract: Antimicrobial proteins comprise a significant component of the acute innate immune response to infection. They are induced by pattern recognition receptors as well as by cytokines of the innate and adaptive immune pathways and play important roles in infection control and immunomodulatory homeostasis. Lipocalin 2 (siderocalin, NGAL, 24p3), a siderophore-binding antimicrobial protein, is critical for control of systemic infection with Escherichia coli; however, its role in mucosal immunity in the respiratory tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(194 citation statements)
references
References 61 publications
12
181
1
Order By: Relevance
“…This may, also, at least in part, explain the fact that IRAK-M deficiency was associated with enhanced neutrophil recruitment to the lungs during secondary pneumonia following peritonitis (9), whereas it did not influence neutrophil influx during primary airway infection (this study). In the current investigation, IRAK-M deficiency did not enhance the production of either lipocalin 2 or CCL20, both antimicrobial proteins produced by the respiratory epithelium implicated in host defense against respiratory tract infection (24,25 (38).…”
Section: Discussionmentioning
confidence: 95%
“…This may, also, at least in part, explain the fact that IRAK-M deficiency was associated with enhanced neutrophil recruitment to the lungs during secondary pneumonia following peritonitis (9), whereas it did not influence neutrophil influx during primary airway infection (this study). In the current investigation, IRAK-M deficiency did not enhance the production of either lipocalin 2 or CCL20, both antimicrobial proteins produced by the respiratory epithelium implicated in host defense against respiratory tract infection (24,25 (38).…”
Section: Discussionmentioning
confidence: 95%
“…Work to date has focused principally on the proinflammatory and metabolic effects of Lcn2 (11,13,(51)(52)(53)), yet less is known regarding cardiovascular effects. Several studies have now shown that Lcn2 was elevated during ischemia-reperfusion processes and in coronary heart disease and myocardial infarction (12,20,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of lipocalin-2 involves signalling via Toll-like receptor 4 (TLR4) and subsequent NF-kB binding to consensus sequences upstream of the lipocalin-2 promoter (Flo et al, 2004;Li & Chan, 2011), and its production is regulated via IL-1b, IL-17A and other cytokines (Chan et al, 2009;Kolls et al, 2008;Li & Chan, 2011). Although lipocalin-2 is increased in the lungs of mice during infection with Aspergillus fumigatus, lipocalin-2-deficient mice do not demonstrate impaired fungal clearance (Gessner et al, 2012), and lipocalin-2 does not bind to fungal siderophores (Flo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%